PENINGKATAN PRODUKTIVITAS UMKM PEMBUAT KUE TRADISIONAL ACEH MELALUI PENDEKATAN KONSEP LEAN DENGAN METODE VALUE STREAM MAPPING - Fitriadi Fitriadi; Muzakir Muzakir (Universitas Teuku Umar, 2019)
The improvement of SMEs productivity can be seen from the ability of SMEs to make an effective and efficient production process. The problems issued by the Aceh Traditional Cake Maker SMEs above if viewed in more detail occur in the production process. SMEs do not support many production processes that can be increased to be more effective and efficient. During this time, SMEs Makers of Traditional Acehnese Cake feel there is waste that often occurs. However, Aceh's traditional SMEs makers rarely take measurements. In fact, waste really determines business efficiency and will certainly have an impact on productivity and low business profits. The purpose of this study is to allow waste that occurs with the concept of discussing Lean with the method of mapping the flow of values and reducing this waste so as to be able to increase the productivity of MSMEs Traditional Acehnese Cake Makers. The Lean concept will eliminate waste or non-value added activities from a process at the Aceh Traditional Cake Maker SMEs so that activities along the process flow produce Value. The method used to collect waste is Value Stream Mapping (VSM). The results of this study obtained waste that occurs in the process of making cakes waste of waiting time and waste of transportation that occurs in the work element of mixing dough, waste of defective products that occur in the work element of frying. The improvement offered to reduce waste is the activation of production equipment.